“A Bed of Nails”: Professional Musicians’ Accounts of the Experience of Performance Anxiety From a Phenomenological Perspective - Papageorgi, Ioulia; Welch, Graham F. (Frontiers in Psychology, 2020)
Most investigations of musical performance anxiety have employed quantitative methodologies. Whereas such methodologies can provide useful insights into the measurable aspects of the experience in a larger group of participants, the complexity, subtlety and individuality of the emotional experience and the importance of the individual’s interpretation of it are often overlooked. This study employed a phenomenological approach to investigate the lived, subjective experience of performance anxiety, as described in professional musicians’ narratives. Semistructured interviews with four professional musicians (two males, two females) specializing in Western classical and jazz music genres were conducted and analyzed using Interpretative Phenomenological Analysis (IPA). The analysis revealed the presence of four overarching themes: (1) Intensity of performance anxiety experience, (2) perceived effects, (3) development of coping strategies and (4) achieving release from anxiety. Findings suggest that the lived experience of performance anxiety is multifaceted, characterized by a physical and a psychological dimension. Interpretative Phenomenological Analysis is a useful research tool that can facilitate our understanding of the subjective experience of performance anxiety (how it is felt and understood at an individual level) and can thus be useful in the development of tailor-made intervention programs for musicians.